Factors influencing the consumption of aged cheeses among people associated with medical community – survey study - Machowiec, Piotr Artur; Leszczyk, Patryk; Niemirski, Dominik Paweł; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2019)
Introduction: Long-maturing cheeses are gaining more followers lately. Their sustainable inclusion in the daily diet, in view of their nutritional values and the best source of bioavailable calcium, brings them the recommendations of doctors, dieticians. The aim of the study is evaluation of factors influencing the consumption of aged cheeses among people associated with medical community.Material and methods: Material used in the epidemiological analysis is the results of survey conducted on group of 204 young adults aged 18-24 rating factors influencing the consumption of long-maturing cheeses among the students of medical universities. Results: The survey carried out indicates that 35% of people surveyed do not distinguish long-maturing cheeses from regular cheeses. Of the people surveyed, 47.1% have answered that their cheese purchasing is influenced by the product’s appearance and that irregular holes and natural colour present in cheese are signs of high quality. Simultaneously, 35.3% of the respondents believe that the higher price of long-maturing cheese dissuades them from purchasing such products.Conclusion: The conducted survey suggests that the main factors influencing the consumption of long-maturing cheeses in the medical community are: level of knowledge of health benefits, pricing, outer appearance of the product, and the degree of popularization of healthy nutrition. Yet still a significant percentage of respondents seem not to see the benefits of its consumption, suggesting a need for further education of people in terms of principles of nutrition, and advertising campaigns showing the importance of consumption of dairy products.